ANALISIS KREATIVITAS GURU DALAM PEMBELAJARAN MENGGUNAKAN ALAT UKUR (MAU) KEAHLIAN TEKNIK PEMESINAN DI KABUPATEN SLEMAN PADA TAHUN AJARAN 2012/2013 - Setuju Setuju (Jurnal Taman Vokasi, 2013)
This research objective is describing teacher creativity in using measurement tool learning of Senior High School in Sleman. This research design is survey. Survey research is one kind of descriptive research. Subject in this research are all teacher that teach subject measurement tool in senior high school of Engineering program. Instrument that use in this research is quesionare of teacher creativity in learning with perspective in meaning of teaching and learning. Analyzing of data is using descriptive statistic through percentage. This research result shows teacher measurement tool from two SMK (SMK Prambanan and SMK Depok) have good creativity and the other still have enough creativity.